1989
DOI: 10.1115/1.3250737
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Convection in an Annulus of Large Aspect Ratio

Abstract: ixed Convection in an Annulus of Large Aspect Ratio Mixed convection in an annulus of large aspect ratio is studied. At an aspect ratio of 100, the effect of wall curvature is minimal, and both the base flow and the stability characteristics approach those of a two-dimensional channel flow. The linearstability results demonstrate that the fully developed flow is unstable in regions of practical interest in an appropriate parameter space. Consequently, commonly assumed steady parallel countercurrent flows in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Orszag (1971) and more recently by Davey (unpublished, but see Drazin & Reid 1987, p. 205) who obtained: Re: = 5772.2218, a: = 1.020547, and c: = 0.2640003. Furthermore, our Gr,-Re parameter space is in excellent agreement with the one computed by Yao & Rogers (1989) (they display theirs in the Gr,/Re-Re parameter space). We note that for a range of Reynolds numbers somewhat larger than [Re,/ there exist regions where an increase in Grashof number has a stabilizing influence on the predominantly pressure-gradient driven flow.…”
Section: Resupporting
confidence: 81%
See 3 more Smart Citations
“…Orszag (1971) and more recently by Davey (unpublished, but see Drazin & Reid 1987, p. 205) who obtained: Re: = 5772.2218, a: = 1.020547, and c: = 0.2640003. Furthermore, our Gr,-Re parameter space is in excellent agreement with the one computed by Yao & Rogers (1989) (they display theirs in the Gr,/Re-Re parameter space). We note that for a range of Reynolds numbers somewhat larger than [Re,/ there exist regions where an increase in Grashof number has a stabilizing influence on the predominantly pressure-gradient driven flow.…”
Section: Resupporting
confidence: 81%
“…We next formulate the linear stability problem of this flow, and subsequently solve the resulting perturbation equations using an integral Chebyshev pseudo-spectral method. The primary conclusions of the study for Pr = 0.71 are that: (i) the instability is almost always oscillatory; (ii) for temperature differences smaller than a critical value, the instability is always shear driven but the character changes as a function of Reynolds number in a way similar to that found by Yao & Rogers (1989); (iii) for temperature differences greater than a critical value, a new mode of instability (due entirely to non-Boussinesq effects) is found which is purely thermal in character in that the disturbance energy is gained from the potential energy associated with the buoyant forces, and is analogous to but not the same as the type of instability found for Pr > 12.45 in the Boussinesq case; (iv) there exists a critical Reynolds number in the non-Boussinesq regime at which the instability switches between different modes associated with shear.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…However, recent work has shown that fully developed mixed convection flows in vertical ducts are highly unstable due to thermally-induced instabilities [1][2][3][4]. [7].…”
Section: Introductionmentioning
confidence: 99%